ADVANCED ENCRYPTION AND EXTENDED AUTHENTICATION FOR WIRELESS LAN - GSR, EMIL SELVAN; N, GAYATHRI; S, RAKESH KUMAR; RAI, ANKUSH; R, JAGADEESH KANNAN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Wireless networking technology is becoming increasingly popular but, at the same time, has introduced many security issues. WEP standards are followed in WLANs for providing security. But WEP is fatally crippled by the fact that WEP keys are the same for all users, all sessions and never changes and its poor implementation of the RC4 encryption scheme. The authentication mechanism is based on aÂ simple challenge-response protocol. The main problem with the previously used method was same key was used for both encryption and authentication. But the proposed authentication is by means of certificates using Extensible Authentication Protocol and a session key is transferred after successful authentication between mobile node and server. This session key is then used for encrypting messages using Advanced Encryption Standard between mobile node and server.